Effects Of On Job Information Technology Security Training On Network Security Management - Oguk, Charles Ochieng (IJRDO -Journal of Computer Science Engineering, 2015)
This study has been conducted to determine the effects of (on job) I.T security training on the management of computer network’s security within Kenyan public Universities. Computer networks in Kenyan institutions have in the recent past experienced a number of security compromises, leading into huge financial loses and breaches of system integrity. Hacking communication channels is a daily occurrence in Kenya. Findings by Deloitte Kenya Ltd indicated that East African business computer networks are still vulnerable to attack, fraud and confidentiality breaches. To reduce the problem of hacking computer networks, institutions conduct on job- Information Technology security training for I.T professionals. While some people perceive the training to bring forth positive returns, others feel it may expose the internal I.T systems to even more risks. Despite the uncertainty, institutional managers continually invest heavily on IT security training. This has led to a focused attention in on job IT security Training and its effects on computer network security within the Kenyan public Universities, to analyze how its management is affected by this training. The major outcome of the study has been a positive correlation between the training and all the elements of computer network security management, thus determininhg the relationship under study. The findings could be significant to organizational policy makers, security trainers and IT heads in managing University network security more effectively.